Estimating the gradient of vector fields via div and curl in variable exponent Sobolev spaces. (March 2020) - Sin, Cholmin; Ri, Sin-Il
Abstract: We show an estimate of the gradient of vector fields u in terms of div u and curl u in vector-valued variable exponent Sobolev spaces with vanishing normal component on the boundary in simply connected 3D-domains.